Legacy of Faster, Better, Cheaper? Cost, Schedule, and Performance Objectives: Understanding the Impact of NASA Policy on Perceptions of Failures. (November 2022) - Eaton, Casey; Patel, Shivani; Glandon, K. Loveday; Weger, Kristin; Mesmer, Bryan; Moreland, Robert
Abstract: This research examines perceptions of failure at the US National Aeronautics and Space Administration (NASA) and NASA's "faster, better, cheaper" movement of the 1990s, identifying how subsequent perceptions, policies, and practices reflect and react to this former ideology in regards to perceptions of failure. Thirty-one NASA participants were surveyed regarding their definitions of failure and perceptions of causes of failure. Regarding failure, participants believed optimistic schedule and budget planning leads to failures and also believed that NASA was neutral on prioritizing prevention of budget overruns and schedule delays. Participants often defined and perceived failures in three areas of schedule, performance, and cost objectives, which are similar to the terms "faster, better, cheaper." Associated NASA documentation, including strategic plans, is investigated, identifying that language regarding failure and success at NASA often involves these three areas. The examination of NASA documentation suggests potential evolution in policy, subsequent to the faster, better, cheaper era. Potential impacts in NASA policy and practice resulting from the FBC ideology are introduced: an absence and return to language of risk acceptance, a continued emphasis on science mission funding, and a gradual reduction in NASA civil servant workforce. The findings of this research provide insight into the operationalization of the three areas emphasized in the faster, better, cheaper ideology, their use in NASA documentation, and acknowledgment by NASA participants.